KEBUTUHAN FASILITAS POKOK PELABUHAN PERIKANAN PANTAI LAMPULO 15 TAHUN MENDATANG (Main Facility Necessity of Lampulo Coastal Fishing Port for 15 Years for the Future) - Fauzi Syahputra; Anwar B. Pane; Ernani Lubis; Budhi H. Iskandar (Bogor Agricultural University, 2015)
ABSTRACTLampulo fishing port located in Banda Aceh. This port categorized as type C. The activity in Lampulo very dense, it is suspected due to inadequate of facilities available at the port. The aims of this study is to determine the projected increase in the production volume of the catch; determine the projected increase in the number of fishing boats; determine the needs of the dock, and harbor, for the current and future needs of 15 years. This research was conducted at the Lampulo fishing port in Banda Aceh by using a case study method. Calculation of the dock and harbour needs presently and in the next 15 years by using statistical data, namely the catch production (1), the number and size of vessel (2), direct measurement of results data objects i.e. jetty length (1), pond depth (2), ships length (3), direct observations data of the research object, namely dock facilities condition (1) port (2), the maximum draft of vessels (3) and the distance between the ship while tethered in the harbour. Based on projections of production, the total production volume in Lampulo reached 14,096 tons in 2027 or increased by 114%, but became decreased in 2028-2029 by 3,6% when compared with the production volume in 2027. The projected number of vessel fleet reached 822 units or an increase of 112% in 2029. Projected increase the size of the dock and the depth of the pool is needed for the next 15 years in the amount of 831m for landing docks and 757m for loading docks. It also required the addition of the port into a vast pool of 224.497 m2 and the depth of the pool minus 3,4 m.Keywords: development, main port facilities, vessel——-ABSTRAKPelabuhan Perikanan Pantai (PPP) Lampulo terletak di kota banda Aceh. Pelabuhan ini adalah pelabuhan perikanan tipe C. Aktivitas di Pelabuhan Lampulo sangat padat, hal ini diduga akibat kurang memadainya fasilitas yang tersedia di pelabuhan tersebut. Tujuan dari penelitian ini adalah menentukan proyeksi peningkatan volume produksi hasil tangkapan; menentukan proyeksi peningkatan jumlah kapal perikanan; menentukan kebutuhan dermaga, dan kolam pelabuhan, untuk saat ini dan kebutuhan 15 tahun kedepan. Penelitian ini dilakukan di Pelabuhan Perikanan Pantai Lampulo Banda Aceh. Metode yang digunakan adalah studi kasus. Perhitungan kebutuhan dermaga dan kolam pelabuhan saat ini dan 15 tahun kedepan menggunakan data statistik yaitu produksi hasil tangkapan (1), jumlah dan ukuran kapal (2), data hasil pengukuran langsung objek penelitian yaitu panjang dermaga (1), kedalaman kolam (2), panjang kapal (3); data hasil pengamatan langsung terhadap objek penelitian yaitu keadaan fasilitas dermaga (1), kolam pelabuhan (2), draft maksimum kapal yang paling besar (3) dan jarak antar kapal saat bertambat di pelabuhan. Berdasarkan proyeksi produksi, total volume produksi di PPP Lampulo mencapai 14,096 ton pada tahun 2027 atau meningkat sebesar 114%, namun mengalami penurunan pada tahun 2028-2029 sebesar 3,6% jika dibandingkan dengan volume produksi tahun 2027. Adapun proyeksi jumlah armada kapal penangkapan terjadi peningkatan mencapai 822 unit atau sebesar 112 % pada tahun 2029. Proyeksi penambahan ukuran dermaga dan kedalaman kolam yang dibutuhkan untuk 15 tahun mendatang yaitu sebesar 831 m untuk dermaga pendaratan dan 757 m untuk dermaga muat. Selain itu juga diperlukan penambahan luas kolam pelabuhan menjadi 224,497 m2 dan kedalaman kolam minus 3,4 m.Kata kunci: pengembangan, fasilitas pokok pelabuhan, kapal